Regulatory agilities impacting review timelines for Pfizer/BioNTech’s BNT162b2 mRNA COVID-19 vaccine: a retrospective study - Patel, Prisha; Macdonald, Judith C.; Boobalan, Jayanthi; Marsden, Matthew; Rizzi, Ruben; Zenon, Marianne; Ren, Jinma; Chu, Haitao; Cappelleri, Joseph C.; Roychoudhury, Satrajit; O’Brien, Julie; Izaki-Lee, Konoha; et al. (Frontiers in Medicine, 2023)
The appropriate use of regulatory agilities has the potential to accelerate regulatory review, utilize resources more efficiently and deliver medicines and vaccines more rapidly, all without compromising quality, safety and efficacy. This was clearly demonstrated during the COVID-19 pandemic where regulators and industry rapidly adapted to ensure continued supply of existing critical medicines and review and approval of new innovative medicines . In this retrospective study, we analyze the impact of regulatory agilities on the review and approval of Pfizer/BioNTech's BNT162b2 mRNA COVID-19 Vaccine globally using regulatory approval data from 73 country/regional approvals. We report on the critical role of reliance and provide evidence that demonstrates reliance approaches and certain regulatory agilities reduced review times for the COVID-19 vaccine. These findings support the case for more widespread implementation of regulatory agilities and demonstrate the important role of such approaches to improve public health outcomes.